1997
DOI: 10.1111/j.1442-9993.1997.tb00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of stocking with the cryptogamic soil crust of a semi‐arid rangeland in southwest Queensland.

Abstract: The soil crust community from a sub-tropical grassland in southwest Queensland was found to include 34 taxa with cyanobacteria, other algae, lichens, fungi, mosses and liverworts represented. Cyanobacteria and liverworts were the major components of the cryptogamic cover. This is a significant component of the biodiversity of the region. Changes in the structure of this community were significantly correlated with distance firom a linear water supply (bore drain) and with dung density. It was concluded that ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
8
31
0
Order By: Relevance
“…High disturbance rates by cattle are associated with low levels of crust (e.g. Anderson et al, 1982b;Hodgkins & Rogers, 1997); it is possible that the high values of crust reported here reflect the absence of pronghorn antelope now extirpated from the site.…”
Section: Field Datamentioning
confidence: 75%
“…High disturbance rates by cattle are associated with low levels of crust (e.g. Anderson et al, 1982b;Hodgkins & Rogers, 1997); it is possible that the high values of crust reported here reflect the absence of pronghorn antelope now extirpated from the site.…”
Section: Field Datamentioning
confidence: 75%
“…In the early 1990s, Rogers' work was followed by a comprehensive study of both lichens and bryophytes in semiarid and arid New South Wales (Eldridge 1996a;Tozer 1996, 1997a,b). During the past decade, there has been renewed interest in the role of biological crusts and their associated organisms in other areas such as subtropical southern Queensland (Rogers 1994;Hodgins and Rogers 1997;Page 1997).…”
Section: Biological Soil Crusts At a Regional Scalementioning
confidence: 99%
“…These disturbances are caused by surface trampling by the livestock hooves. Grazing reduces the total biocrust cover (Beymer and Klopatek 1992;Daryanto and Eldridge 2010;Golodets and Boeken 2006;Hodgins and Rogers 1997;Ponzetti and McCune 2001;Thomas 2012) and biomass (Beymer and Klopatek 1992) while increasing the biocrust cover spatial variability (Gomez et al 2012;Pietrasiak et al 2011). Grazing reduces biocrust richness (Ponzetti and McCune 2001;Root and McCune 2012) and alters biocrust composition, e.g., by increasing cyanobacterial cover at the expense of lichens (Eldridge et al 2000a).…”
Section: Negative and Unequivocal Effects Of Grazingmentioning
confidence: 97%